FORMATION OF DIAGNOSTIC MODEL OF WORKING EFFICIENCY OF AIRCRAFT COMPLEXES - Сильнягін, А. О. (Proceedings of National Aviation University (archive), 2021)
The stages of recovery of electrified complexes are considered. The diagnostic model of working capacity in the form of a matrix of states and algorithm of the organization are offeredinformation database for automated search and localization of the place of failure.